Barriers and facilitators of physical activity in nursing students of the VIII cycle, from a private university in Chiclayo, 2023 - Espinoza Lindo, Jhan Carlos (2024)
Objective: Analyze the barriers and facilitators of physical activity in nursing students, from a private university in Chiclayo, 2023. Method: The qualitative descriptive study, whose study population was 65 students enrolled in the VIII cycle in the 2023-II semester; The sample was determined by saturation and redundancy, non-probabilistic sampling for convenience, obtaining 15 participants; The semi-structure interview was used to collect data. The data were examined through content analysis and criteria of ethical and scientific rigor were met. Results: A) Physical activity barriers in nursing students, having the subcategories: a) Lack of time due to academic load, economic resources and infrastructure to carry out physical activity, b) Absence of external motivation to carry out physical activity, c) Physical limitations and attitude towards physical activity. B) Facilitators of physical activity in nursing students, with the following subcategories: a) Availability of resources to carry out physical activity, b) External support to carry out physical activity, c) Knowledge of the benefits of physical activity for health care. health and aesthetics. Conclusions: The facilitators and barriers for physical activity in university nursing students confront each other, while some encourage it, others inhibit it, as is the case of time management, infrastructure and economy, in addition to the social environment and motivation.